Mangroves in Nipah Panjang Village: Spatial Distribution and Utilization - Atunnisa, Rifa'; Fariz, Trida Ridho; Jabbar, Abdul; Permana, Pawit Indra; Rahmawati, Dwi; Sultan, Habil (Indonesian Journal of Conservation, 2025)
Nipah Panjang Village in Kubu Raya Regency, Indonesia, has diverse mangrove forest vegetation. Meanwhile, the mangrove forest in Nipah Panjang Village has the potential threat of deforestation, so it is necessary to develop a management strategy. A mangrove management directive can be compiled with mangrove biophysical data and the social conditions of the surrounding community. Therefore, this study aims to examine the distribution of mangrove forest areas and their utilization by the community in Nipah Panjang Village. The method used in this study was GIS analysis to determine the distribution of mangrove forest areas. In this study, observations and interviews were carried out to determine the use of mangrove forests. The study results show that from 2013 through 2018, there was around 3.12 Ha of deforestation. Deforestation that occurred was much lower than the previous year. It was due to the implementation of a devolution policy that granted village forest permits in Nipah Panjang Village. Currently, the forms of utilization of mangrove forests in Nipah Panjang Village are the farming (apiculture)  of kelulut honey, forest honey farming, and crab farming with the concept of silvofishery and the development of ecotourism. This form of utilization needs to be maximized so that the community's welfare increases, ultimately maintaining the mangrove forest.